(untitled)
lkfgR; dk lacy fufoZoknr% lekt ghgS vkSj lkekftd ;FkkFkZ ls tqM+k lkfgR; vR;ar izkekf.kd] izlafxd vkSj lthogksrk gSA ,sls lkfgR; ltZu ds fy, lkfgR;dkj esa iw.kZr% lkekftd vkSj lkfgR;dizfrc/nrk;sa vo’; gksuh pkfg;sA dguk u gksxk fd lkfgR;dkj dk drZO; ek= lkekftdfp=.k rd gh lhfer ugha gS] izL;qr mls viuh ys[kuh ds